2005
DOI: 10.1111/j.1469-1795.2005.00004.x
|View full text |Cite
|
Sign up to set email alerts
|

Wildlife conservation and animal temperament: causes and consequences of evolutionary change for captive, reintroduced, and wild populations

Abstract: We argue that animal temperament is an important concept for wildlife conservation science and review causes and consequences of evolutionary changes in temperament traits that may occur in captive-breeding programmes. An evolutionary perspective is valid because temperament traits are heritable, linked to fitness and potentially subject to intense selection in captivity. Natural, sexual and artificial selection can cause permanent shifts in temperament, reducing the diversity of temperament traits, diversity … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
195
0
2

Year Published

2010
2010
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 253 publications
(199 citation statements)
references
References 88 publications
2
195
0
2
Order By: Relevance
“…Being resident or little-ranging rather than migratory also tends to be beneficial in terms of invasion success [29,43,44]. For example, resident parrot species are more likely than migratory species to successfully establish 12 themselves in new locations [44].…”
Section: Resident Versus Migratory Lifestylementioning
confidence: 99%
“…Being resident or little-ranging rather than migratory also tends to be beneficial in terms of invasion success [29,43,44]. For example, resident parrot species are more likely than migratory species to successfully establish 12 themselves in new locations [44].…”
Section: Resident Versus Migratory Lifestylementioning
confidence: 99%
“…For example, free-living animals may reside in areas impacted or provisioned by humans, resulting in effects on their behavior and evolution (McDougall, Réale, Sol, & Reader, 2006). Indeed, social learning may be a key part of allowing animals to cope with human impacts (Lee, 1991;Reader & Laland, 2003a;Whitehead, 2010).…”
mentioning
confidence: 99%
“…However, a variety of theoretical contributions have suggested that ity, are maladaptive in the wild (e.g., tolerance of humans or extreme boldness). Through the link with heritable temperaments, these factors may also affect genetic diversity (McDougall, Réale, Sol, & Reader, 2006).…”
Section: Management/conservation Instrumentsmentioning
confidence: 99%